Religious networks in the Roman empire the spread of new ideas - Collar, Anna 1979- (Cambridge University Press, 2013)
The first three centuries AD saw the spread of new religious ideas through the Roman Empire, crossing a vast and diverse geographical, social and cultural space. In this innovative study, Anna Collar explores both how this happened and why. Drawing on research in the sociology and anthropology of religion, physics and computer science, Collar explores the relationship between social networks and religious transmission to explore why some religious movements succeed, while others, seemingly equally successful at a certain time, ultimately fail. Using extensive epigraphic data, Collar provides new interpretations of the diffusion of ideas across the social networks of the Jewish Diaspora and the cults of Jupiter Dolichenus and Theos Hypsistos, and in turn offers important reappraisals of the spread of religious innovations in the Roman Empire. This study will be a valuable resource for students and scholars of ancient history, archaeology, ancient religion and network theory